Genetic Counseling in Portugal: Education, Practice and a Developing Profession. Issue 4 (3rd March 2015) - Paneque, Milena; Mendes, Álvaro; Saraiva, Jorge; Sequeiros, Jorge
Abstract: Portugal is one of the European countries where genetic counseling is emerging as an independent clinical and scientific field, paralleling the international expansion of this profession. Important steps have been consistently made towards establishing safe and ethical genetic counseling, delivered by adequately trained professionals. In 1998, Clinical Genetics was recognized in Portugal as a medical specialty. Eleven years later, the first generation of Portuguese (non MD) genetic counselors started a master level training programme at the University of Porto.